Descoloração e degradação do azo corante vermelho BR por ozonização - Trevizani, Jéssica Luiza Bueno (2015)
The textile industry is responsible for generating wastewater with high organic content, color and toxicity. The direct objective of this study was to evaluate the hum dye removal efficiency azo-Reactive (Red BR) by ozonation process in pH variations and initial dye concentration. For two solutions: dye plus aqueous solution (Solution 1) and synthetic effluent solution plus dye (Solution 2). To this end, tests were performed at pH 4 (acid), pH 7 (neutral) and pH 10 (alkaline) and the initial dye concentration varied among 50, 100 and 150mg / L As samples were performed from 15 to 15 minutes and the parameters were analyzed. for Solution 1 were: temperature, color removal, turbidity, dissolved ozone, off-gas and ozone consumed. For solution 2, besides these parameters, was also analyzed the removal of organic matter (COD). The rate of ozonation has occurred up to a significant removal of color (> 90%) and between 60 and 240 min.The Ozone production used in this work was a Maximum obtained with Generator 0702 GO3 / h in air flow Maximum (15 L / min). The Maximu m Efficiency of transfer Ozone to the net was 73% in alkaline medium (pH 10) and minimum under acidic conditions (pH 4) For both analyzed solutions. through the application of the central compound design (DCC) and Polling Surface Graphics, it is possible to check the initial dye concentration factors of influence (Factor 1) and pH (Factor 2) in the Variable Voting dye removal. This can be observed as forms of Influence of the initial dye concentration and more significant is that the influence of pH dye removal efficiency. Maximum efficiency removal was 98% For Solution 1 and 2 sat pH 10:04 and initial concentration of dye 50 mg / L. In order to analyze the toxicity of solutions, the before and after process of ozonation, tests were performed as toxicity test with the body similis daphinia and found toxicity at all samples. During this work, it was observed that the ozonation has results in efficient oxidation of dye textile Red BR in all pH variations and dye concentration.